Synthesis of Polyaniline Nanocomposites in Water/Ethyl Acetate Solution by Using Various Surfactants - Eisazadeh, H.; Mahmoodi, S.; Madaeni, S. (Asian Journal of Chemistry, 2010)
Polyaniline nanocomposites were prepared in the aqueous/non-aqueous media by using ammonium persulphate as an oxidant in the presence of various surfactants such as sodium dodecylbenzenesulfonate, poly(vinyl alcohol) and hydroxypropylcellulose. Polyaniline nano-composites were characterized in terms of conductivity, morphology, yield, particle size and chemical structure. The results indicate that the morphology, yield, particle size and conductivity of products are dependent on the type of surfactant. Also, the structure of obtained product was determined by FTIR spectroscopy. The results show that the intensity of peaks is dependent on the type of surfactant.